Lower Limb Unilateral and Bilateral Strength Asymmetry in High-Level Male Senior and Professional Football Players - Espada, Mário C.; Jardim, Marco; Assunção, Rafael; Estaca, Alexandre; Ferreira, Cátia C.; Pessôa Filho, Dalton M. [UNESP]; Verardi, Carlos E. L. [UNESP]; Gamonales, José M.; Santos, Fernando J. (MDPI, 2023)
This study sought to assess the relationship between different jumping asymmetries and associated performance variables in high-level male senior and professional football players. Nineteen football players with at least 12 years of training experience (23.2 ± 3.1 years of age; 75.2 ± 4.8 kg of body mass and 181 ± 0.06 cm of height) participated in this study performing countermovement jump (CMJ), squat jump (SJ), single-leg CMJ and drop jump (DJ), associated performance variable eccentric utilization ratio (EUR), stretch-shortening cycle (SSC), bilateral deficit (BLD), and limb symmetry index (LSI) were determined. High correlations were observed between different methodologies of jump tests and associated performance indicators (SSC, BLD, EUR), except LSI. Moreover, CMJ and SJ results were different (p < 0.05), but no differences were found between interlimb in CMJ (p = 0.19) and DJ (p = 0.14). Between the same limbs and different jumps differences were detected in CMJ and DJ (p < 0.01), and it has also been found that the laterality effect size on strength was small in CMJ (ES = 0.30) and DJ (ES = 0.35). LSI between CMJ and DJ was not different despite higher mean values in CMJ, and although mean BLD was positive (>100%), the results highlight the need for individual evaluation since eight players scored negatively. An in-depth and accurate analysis of performance in preseason screening jump tests should be considered, aiming to detect injury risk, specifically evaluating different jumping test methodologies, and determining jumping associated performance variables for each test, namely EUR, SSC, BLD, and LSI. Specific muscle-strengthening exercises could be implemented based on this study results and outcomes, aiming to reduce injury risks and lower extremity asymmetries and to enhance individual football performance in high-level male senior and professional football players. Sports institutions should pay special attention regarding potential health problems in athletes exposed to daily high training loads.
Keywords: injury risk; interlimb; performance; soccer; strength; symmetry